2012
DOI: 10.1149/2.048207jes
|View full text |Cite
|
Sign up to set email alerts
|

Computational Exploration of Ultra-High Current PEFC Operation with Porous Flow Field

Abstract: A comprehensive 2D+1 computational model has been developed to explore the operation of a polymer electrolyte fuel cell (PEFC) with a porous flow field, also called open metallic element (OME), in the ultra-high current density regime (>2A/cm 2 ). The computational model has been validated to a greater extent than previously published multi-phase models, including in-situ experimental measurement of performance, high frequency resistance (HFR) and net water drag coefficient under a wide range of input relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…Their results indicated that α NWD increased with i, though α NWD remained negative when i was less than about 2.5 A cm −2 . Zheng and Srouji et al 19,20 reported the dependency of α NWD on T cell at a constant i of 2 A cm −2 using the same cell as Zheng et al, 18 and reported that α NWD increased with T cell and turned from negative to positive when T cell exceeded a certain threshold value. Gandomi et al 21,22 investigated the effect of MPL properties on α NWD under various conditions, including cathode-dry condition.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Their results indicated that α NWD increased with i, though α NWD remained negative when i was less than about 2.5 A cm −2 . Zheng and Srouji et al 19,20 reported the dependency of α NWD on T cell at a constant i of 2 A cm −2 using the same cell as Zheng et al, 18 and reported that α NWD increased with T cell and turned from negative to positive when T cell exceeded a certain threshold value. Gandomi et al 21,22 investigated the effect of MPL properties on α NWD under various conditions, including cathode-dry condition.…”
mentioning
confidence: 96%
“…The effect of operating parameters (cell temperature, pressure, stoichiometric ratio and relative humidity of the inlet gases) and the specifications of the cell components (membrane, electrode, and gas diffusion layer) on the water transport behavior in the cell has been examined by evaluating α NWD . [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Some of those studies focused on the effect of a micro-porous layer (MPL) on the water transport behavior in the cell, 12,13,16,17 because there is a hypothesis that the presence of an MPL on the cathode gas diffusion layer (GDL) would enhance the back-diffusion of water through the membrane from the cathode to anode. 23,24 Based on water balance measurements, Kim et al 16 reported that water transport toward the anode from the cathode increased significantly when an MPL was added to GDL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study provide a comparison between conventional parallel C/L design and an open metallic element for the first time in literature, and show different origins of performance limitation of the two designs. The experimental work also provides validation data for simultaneous modeling efforts of the open metallic element design [23].…”
Section: Introductionmentioning
confidence: 98%
“…Among all types of electrolyzer cell systems, PEMEC is providing a promising solution for hydrogen and oxygen production and receiving more and more attention due to their higher energy efficiency/density, faster charging/discharging, and a more compact design [1][2][3][4][5]. A PEMEC has a similar configuration and operating components to a PEM fuel cell (PEMFC) [6][7][8][9][10][11]. Figure 1 shows a three-dimensional geometry schematic of a typical single-cell PEMEC, which consists of flow channels, liquid/gas diffusion layers (LGDL), catalyst layers (CL), and the PEM.…”
Section: Introductionmentioning
confidence: 99%